Seeing Through the Eyes of the Other Using Process Recordings - Schneider, Dana A.; Rodriguez-Keyes, Elizabeth; Keenan, Elizabeth King (Clinical Supervision Activities for Increasing Competence and Self-Awareness, 2014)
This chapter describes a two-step process including videotaping and process-recording activities to facilitate self-awareness and the expression of empathy and acceptance toward other points of view. These activities are designed for beginning student clinicians who are currently completing their coursework and their first clinical internship. The first step of videotaping helps clinicians become more aware of their inner thoughts, feelings, beliefs, and personal values. This first step also helps participating clinicians become more aware of their nonverbal communication with clients, helping them assess how their internal experiences of empathy and acceptance match what is being conveyed nonverbally to their clients. The second step of the activity, process recording, helps clinicians reflect on their ability to use self-awareness to analyze their inner experiences and their outer expressions of empathy and acceptance (both verbal and nonverbal) while still being attuned to their clients' communication.
Section: 4 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781394259335.ch4
Keywords: dept.swk; nonverbal communication; process-recording activities; self-awareness; videotaping

Alcohol Use Among Latino Males: Implications for the Development of Culturally Competent Prevention and Treatment Services - Colon, E. (Alcohol Use/Abuse among Latinos : Issues and Examples of Culturally Competent Services, 2014)
This paper examines the factors surrounding the use of alcohol among Latino males. Prevention and treatment strategies for the provision of culturally competent treatment services are proposed, based on an analysis of the literature. © 1998 by The Haworth Press, Inc. All rights reserved.
Journal Abbreviation: Alcohol Use/Abuse among Latinos : Issues and Examples of Culturally Competent Services
Keywords: dept.swk

Feeding relationships: foodways and social networks in a women’s prison - Smoyer, Amy B. (Affilia, 2014)
Research has demonstrated the importance of supportive relationships and social networks to prisoners’ psychosocial outcomes, especially for women. Understandin...
25 citations (Crossref) [2023-10-31] Publisher: SAGE PublicationsSage CA: Los Angeles, CA
Keywords: dept.swk; peer-reviewed

Dealing food: Female drug users’ narratives about food in a prison place and implications for their health - Smoyer, Amy B.; Blankenship, Kim M. (International Journal of Drug Policy, 2014)
18 citations (Crossref) [2023-10-31]
Keywords: dept.swk

Setting the stage: creating study sites that promote the safety and dignity of research participants - Smoyer, Amy B.; Rosenberg, Alana; Blankenship, Kim M. (Social Work Research, 2014)
The U.S. Department of Health and Human Services' (HHS) Code of Federal Regulations regarding Protection of Human Subjects (45 C.F.R. part 46) provides guidance
1 citations (Crossref) [2023-10-31]
Keywords: dept.swk

Hunger in a “Land of plenty”: A renewed call for social work action - Libal, Kathryn; Tomczak, Stephen Monroe; Spath, Robin; Harding, Scott (Social Work, 2014)
4 citations (Crossref) [2023-10-31] tex.eissn: 1545-6846 tex.unique-id: ISI:000343058300014
Keywords: Child; Cooperative Behavior; Cross-Sectional Studies; Financing; Government; Food Assistance; Food Supply; Forecasting; Humans; Hunger; Interdisciplinary Communication; Politics; Poverty; Social Welfare; Social Work; Socioeconomic Factors; United States; catering service; child; cooperation; cross-sectional study; dept.swk; economics; financial management; food assistance; forecasting; human; hunger; interdisciplinary communication; organization and management; politics; poverty; social welfare; social work; socioeconomics; statistics and numerical data; trends

This is common factors - Cameron, Mark (Clinical Social Work Journal, 2014)
Common factors are conditions and processes present in, among, and surrounding participants in clinical work. In the past 20 years, increasing attention and research on common factors has generated a great deal of discussion in clinical psychology, psychiatry, marriage and family therapy, and to a lesser extent, social work. While there is no single definition of common factors, they are generally discussed as the non-technical aspects of therapeutic work-such as the relationship between the practitioner and client and the expectancy of the client-that have been shown to be associated with successful outcomes. Common factors also include attributes of the practitioner and client, the support system of the client, the institutional and organizational conditions in which the practitioner practices, and also the strategic actions employed by the practitioner, client, and all those involved in the work that promote change. This paper will discuss key concepts in a common factors practice perspective and how evidence is used by common factors practitioners, highlight features of common factors practice, and suggest implications for developing a common factors practice approach.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-423-644-681-260 tex.type: [object Object]
Keywords: Common factors; Evidence; Practice research; Technique; Therapeutic relationship; dept.swk

Beyond the manual: using research and evidence in social work practice - Grady, Melissa D.; Keenan, Elizabeth King (Clinical Social Work Journal, 2014)
There is a growing divide in social work between those that believe social work interventions should be based on either art or science. We argue that these positions create a false dichotomy within the profession, possibly due to the language associated with clinical work and research. In this introduction article of the Special Issue: Beyond the Manual, we outline the debate within social work around the art and science split and then offer a new approach to framing the issue. We argue that social workers are regularly approaching their work with clients using art and science simultaneously and describe a new frame for the profession. In an effort to articulate and promote this new frame, this special issue was born. This introductory article concludes with a brief description of the topics and articles included in the issue to orient the reader to the content included within it.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/115-623-556-720-515 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Clinical judgment; Common elements; Common factors; Evidence-based practice; empirically-supported interventions; Research; dept.swk

From silos to scaffolding: engaging and effective social work practice - Keenan, Elizabeth King; Grady, Melissa D. (Clinical Social Work Journal, 2014)
In this final article of the special issue Beyond the Manual: Using Data and Judgment in Clinical Social Work Practice, we extend the discussion regarding the use of data and judgment. We discuss the multiple sources of data used in practice, including research evidence, client perspectives and experience, moment-by-moment process observation, and client feedback regarding progress towards specific, desired outcomes. We move beyond current debates purporting one framework over another to propose a synthesizing framework that situates evidence-based practice, empirically supported interventions and common elements/mapping and adapting practice within a common factors scaffolding framework. This framework provides a way for social workers to effectively make sound judgments using research and client data within the demands of contemporary practice. The article provides a brief overview of the four practice approaches followed by the proposed scaffolding framework and rationale, and concludes with implications for practice, professional education, and research.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-863-792-919-992 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Common elements; Common factors; Empirically supported interventions; Empirically supported treatments; Evidence-based practice; Research evidence; dept.swk